Le réseau hydraulique à Pompéi (Italie) de l’époque des Samnites à Auguste (fin ive-fin ier s. av. J.-C.) - Federico Giletti (Gallia)
The absence of specific stratigraphic investigations has always made it difficult to gain a deeper understanding of the various aspects of Pompeii’s subsoil. Despite this, the archaeological literature has attempted, on the basis of the few diagnostic elements available, to reconstruct the history of the city’s water management system and its evolution in the context of the site’s urban development. This study pursues this line of research, re-examining its phases and proposals through a wide-ranging analysis of the issues tackled, but above all by proposing a new and systematic approach to the subject, from which it has been possible to take stock of some elements and to verify or arrive at new conclusions on others.While the bibliography concerning certain aspects of Pompeii’s water management is rich, dedicated and in some cases quite comprehensive, regarding which this research has demonstrated the limits of a generic approach absent excavation work, on other topics by contrast the study presented here provided an opportunity for the first time to deepen our knowledge of issues and artefacts and the possibility of bringing together the various topics.With regard to the water supply to the Archaic and Hellenistic city, therefore, it was possible to identify an integrated system of supply to the entire urban space, consisting of catchment wells and cisterns for recovering rainwater from the roofs. With respect to the supply to the archaic city in the early and middle Samnite era, the evidence shows the use and spread across the main urban area of deep artesian wells, designed to intercept and capture the water present in the subsoil of Pompeii’s high ground. In our current state of knowledge, it is possible to identify 28 wells which, though already in use in the Archaic period, were perfectly integrated into the urban organisation of the Samnite city, where they were mainly located in open spaces, at crossroads and along roads. The monumental appearance that, in some cases, frames and marks the outcropping of the deep wells, eloquently portrays the public utility function that these wells must have had in most of the attested cases.On the basis of the research, other types of cisterns in addition to water catchment wells have been identified in the earliest phases of the city of Pompeii, such as the tunnel cistern, a type that was widespread in various contexts in the ancient Tyrrhenian from the Archaic period onwards, and the so-called cylinder or bottle cistern, also evidenced in ancient times and archaeologically documented between the 4th and 3rd centuries BC in a number of Pompeian contexts. While the latter type appears equally in both private and public contexts, the burrow cistern by contrast differs in that it is excavated entirely into the lava stratum and has been demonstrated, as far as we currently know, only on the main outcrops of the lava plateau, such as on the rocky crest of the southern drop in height below insula 2 of Regio VIII.While the type of cistern with a burrow or bainhole seems to have been inspired by models already widespread in Punic-Carthaginian sites in Africa and on the islands and in the Magna-Greek area, cases of cisterns with a burrow collected to several arms primarily bear strong similarities to Etruscan-Latian examples, as does the technique of drainage tunnels entirely excavated in the geological bank and the custom of digging deep artesian wells. It can therefore be said that, just as the Archaic and Early and Middle Hellenistic city received and reworked in its architecture and urban planning knowledge, practice and models taken from both Etruscan-Italic and Greek sources, Pompeii also implemented techniques and devices for water collection and conservation that were clearly derived from the mix of knowledge and engineering practices in use in the most important civilisations evidenced between the Archaic and Early Hellenistic periods in the Tyrrhenian area.With regard to water catchment wells, which may have already been in use in the Archaic age, but were certainly widespread and used in the Samnite city at least until the advent of aqueduct dependent water supplies, it is also possible to trace their historical evolution, which follows the urban development of Pompeii over time.Contrary to the oldest forms of water storage, which seem to have a continuity of use and in some cases coexist with the later chambered cisterns, wells seem gradually to have lost their original function, especially those associated with production contexts or located along minor roads. For their part, wells connected to the nerve centres of the urban road network and to the supply system of thermal buildings would seem to have been in decline, becoming supplementary to the supply provided by the aqueduct pressure system.The collection wells categorically and definitively fell into disuse through the complete obliteration of the reservoir or, if originally in the public sphere, through their assimilation into private property, or even through functional conversion to drains, favoured as it was by the dispersive capacities of the geological subsoil and the considerable depths of the pipe.While this is the information that can be deduced from the analyses conducted on the city of Pompeii’s earliest historical phases, the data that have emerged from the middle and late Samnite periods reveal a change in previous conditions and the adoption of new mechanisms.Between the 3rd and 2nd centuries BC, the introduction of a new urban layout and Pompeii’s entry into Rome’s sphere of influence triggered an urbanistic mutation of the site inspired by the model of the Roman city.Roman-style hydraulic engineering in Pompeii also encouraged the choice of vaulted chamber cisterns, which were often introduced into the city as a complement to the previous storage structures.The chambered cistern type not only reduced the cost of excavating the lava bed, but also made for greater safety in open-air construction and enhanced the static capacity of the walls and cement cover to improve the structural qualities of the cisterns and considerably increase their storage capacity.In particular, the adoption of the sub-type of cistern with multiple, parallel chambers also made it possible, through the principal of the discharge of forces through the vaulted system, to terrace and amplify the spaces available for building.This is what research has shown in the urban construction of Pompeii, which in the course of the 2nd century BC was also focused near the height of the promontory, as attested above all along the southern lava ridge of Regio VIII. Here the archaeological data has made it possible to trace the presence, below the later domus, of buildings from the 2nd century BC, built behind the city walls and basing part of their southernmost rooms on the sequence of cisterns with multiple vaulted chambers. While it is true that the decision to install chambered cisterns to regulate the slope of the hillside may have served to enlarge the building spaces, it is equally plausible that their purpose was also to provide the city wall defences with water reserves to supply the militia in case of siege or fire, in accordance with a common practice in ancient urban design.The military value of some of these cisterns, however, lost its significance after the establishment of the colony, as did walled fortifications. For this reason, the growing tendency to build sumptuous dwellings, with an enviable viewpoint overlooking the Sarno plain below, led to buildings being extended above and beyond the defensive walls, even reusing structural parts that were no longer considered necessary.In the same way, many of the cisterns behind them lost their function, being converted into rooms in the house or used as stairways or corridors.The large basins seem to have retained their function until the advent of the aqueduct system, introduced in Pompeii in the Augustan age. The cisterns initially coexisted with these without significant changes, except for a gradual decline in the maintenance of the structures.On the other hand, a sharp interruption would seem to have occurred between the earthquakes in the 1960s AD and the subsequent reconstruction phases, a period in which many of the old reservoirs, which had long since lost their meaning and function, were probably definitively dismantled and converted into usable spaces.